Smoking behavior of a group of students and their knowledge regarding the health effects of smoking - Altıntaş, K. Hakan; Adıgüzel, M. Oğuz; Koç, Ali Murat; Aralov, Bahtiyar; Yiğit, Eda; Orhan, Elif (Journal of Dependence, 2008)
Objective: To determine and evaluate smoking prevalance, factors affecting smoking prevalance, knowledge regarding health effects of smoking among students at a private secondary and high school in Ankara. Method: On October 3rd, 2007, this cross-sectional study was conducted with the participation of 277 students in Keçiören district of Ankara province. The data were collected with a 30-item questionnaire. Chi-square test was used to test the statistical differences. Results: The mean age of participants was 14.4 ± 1.8 (min – max = 11 – 18) and 54.5% were male. The overall rate of ever smoking was 14.6%. The factors found to be associated with ever smoking were age, being a student at secondary or high school, school success of the student, and buying cigarettes for someone else. Of the students, 49.8% said that there was someone who smokes in their families. Among the diseases caused by smoking, the most known was cancer of lung (94.1%). For the students the most important source of knowledge regarding smoking was television (38.5%). The students’ rate of exposure to passive smoking was 64.5%. Of the students, 67.3% bought cigarettes for someone else in the past. Conclusion: The rate of ever smoking was 14.6%. The factors associated with ever smoking were age, being a student at secondary or high school, school success, and buying cigarettes for someone else.